Animal-Assisted Therapy in palliative care: a scoping review - Palomino-Lázaro, Laura; Rueda-Extremera, María; Cantero-García, María (Frontiers in Psychology, 2024)
Background: Animal-assisted therapy (AAT) is increasingly recognized as beneficial in palliative care, aiming to enhance the well-being of terminally ill patients. Palliative care focuses on holistic support for physical, emotional, social, and spiritual needs. AAT uses animal interactions to alleviate symptoms such as pain, anxiety, and depression, promoting social engagement and emotional comfort. This review assesses AAT's effectiveness in enhancing the quality of life for palliative care recipients. Aim: Synthesizing literature on AAT in palliative care, the review examines its impact on physical symptoms, emotional well-being, social interactions, and overall comfort. By analyzing diverse studies, it aims to elucidate AAT's therapeutic potential and identify research gaps. Design: Systematic review. Data Sources: searches in PubMed, ProQuest, Psychology Database, and Scopus identified relevant studies evaluating AAT interventions in palliative care. Data extraction focused on study characteristics, participant demographics, AAT interventions, and reported outcomes, with rigorous quality assessment. Results: Studies consistently report positive outcomes of AAT in palliative care, including reduced pain, anxiety, depression, and improved mood and well-being. AAT also enhances social interactions and emotional support, albeit with variations in study designs. Conclusion: AAT holds promise for improving quality of life in palliative care by addressing physical, emotional, and social needs. Future research should standardize methodologies, explore mechanisms of action, and optimize AAT integration into comprehensive palliative care strategies. Keywords: palliative care, patients, animal-assisted therapy and quality of life.